THE KNOWLEDGE AND IMPACT OF NURSING CARE FOR PATIENTS WITH END OF LIFE KENNEDY’S END ULCER - da Silva Viana, Darley; Viana Silva, Caio; Alves Gusmão Oliveira, Vinícius (Health and Society, 2023)
Introduction: Kennedy Terminal Ulcer (UTK) is a disease that affects patients at the end of life. It occurs due to physiological changes that damage the body’s homeostatic mechanisms, even with adequate interventions or a high standard of well-being. UTK has a sudden and rapid onset and tissue deterioration evolves over the course of a few hours. In this sense, identification, diagnosis, treatment and adequate management are important for the nursing team in directing and comforting the patient at the end of life. Objective: To recognize, through a bibliographical review, the knowledge and impact of nursing care for patients with Terminal Kennedy Ulcers in the final stage of life. Methodology: This is a descriptive bibliographic review research, built from materials published between 2016 and 2022. To select the texts, an online search was carried out in the VHL Database (Virtual Health Library). We considered 07 publications that met the theme of the study, published in full, with full texts available, in Portuguese, Spanish and English. The keywords investigated were: Kennedy Terminal Ulcer, Terminality, End of life. Results: Regarding nursing knowledge, the absence of early diagnosis or correct diagnosis from the identification of the Ulcer and the lack of knowledge about the characteristics of its development was evidenced. As for the impact of nursing care, it was clear that with the correct diagnosis, there is the preparation of the nursing team and family members for the palliative approach, bringing comfort to the affected person, better instruction for family members, and the team’s assertive direction of nursing for a death without suffering. Final considerations: UTK is a great challenge for nursing, as its commitment goes far beyond the biological scope, it interferes in the way of life of the affected people, their families and social groups. There is still a shortage of scientific studies by the national community, in particular by nurses, demonstrating a deficit of knowledge related to care, and with erroneous classification and identification of the UTK.